MENAKAR EFEKTIFITAS PEMILU SERENTAK DI TENGAH DEMOKRASI ELEKTORAL - Sihabuddin Sihabuddin (Universitas Islam Madura, 2019)
Holding common election is an election proscess of people to fill certain poltical position, there are many postion such as president, vice president vice people, representative regional council (DPD), globally common elections. Election in a broad sense is all processes related to suffrage, election administration and voting behavior. Whereas, in a narrow sense the electoral system is a way which voters can express their political right by voting, which a country is transformed into a seat in parliament or political officials who have three functions in the form of legislation, budgeting and supervision.